Contextual Learning of Science Based on Environmental Problems Around Schools - Ashlan, Said; Firayani, Firayani (PT. Anagata Sembagi Education, 2025)
Science learning in schools often does not connect science concepts with the environmental realities faced by students on a daily basis, this leads to low learning relevance and lack of ecological awareness of students, this study aims to examine the effectiveness of contextual science learning based on environmental problems around schools in improving students' understanding of concepts and concern for environmental issues, this study uses a Systematic approach Literature Review (SLR) by analyzing 27 scientific articles published between 2020–2025, articles were obtained from various reputable databases with inclusion criteria including a focus on environment-based science learning, available in full text, and from primary to secondary education levels, the results of the analysis showed that contextual science learning based on environmental issues significantly improved students' understanding of science concepts, Critical thinking skills, as well as forming a character of caring for the environment, in addition, this approach is effective in integrating students' real experiences with teaching materials, the environment-based contextual approach is a relevant innovative strategy to support meaningful and sustainable science education in schools.